Psychotherapy at the End of Life - Saracino, Rebecca M. (Am J Bioeth, 2019)
Dr. Elisabeth Kübler-Ross is credited as one of the first clinicians to formalize recommendations for working with patients with advanced medical illnesses. In her seminal book, On Death and Dying, she identified a glaring gap in our understanding of how people cope with death, both on the part of the terminally ill patients that face death and as the clinicians who care for these patients. Now, 50 years later, a substantial and ever-growing body of research has identified “best practices” for end of life care and provides confirmation and support for many of the therapeutic practices originally recommended by Dr. Kübler-Ross. This paper reviews the empirical study of psychological well-being and distress at the end of life. Specifically, we review what has been learned from studies of patient desire for hastened death and the early debates around physician assisted suicide, as well as demonstrating how these studies, informed by existential principles, have led to the development of manualized psychotherapies for patients with advanced disease. The ultimate goal of these interventions has been to attenuate suffering and help terminally ill patients and their families maintain a sense of dignity, meaning, and peace as they approach the end of life. Two well-established, empirically supported psychotherapies for patients at the end of life, Dignity Therapy and Meaning Centered Psychotherapy are reviewed in detail.